2022
DOI: 10.3390/ijms23116304
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteomics in Patients with Head and Neck Cancer: Peripheral Blood Immune Response to Treatment

Abstract: In this real-world study, the aims were to prospectively evaluate the expression of inflammatory proteins in serum collected from head and neck cancer patients before and after treatment, and to assess whether there were differences in expression associated with treatment modalities. The mixed study cohort consisted of 180 patients with head and neck cancer. The most common tumor sites were the oropharynx (n = 81), the oral cavity (n = 53), and the larynx (n = 22). Blood tests for proteomics analysis were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The results are presented as normalized protein expression, an arbitrary unit in Log2 scale. The cytokine serum levels have been reported earlier [ 18 ].…”
Section: Methodsmentioning
confidence: 84%
“…The results are presented as normalized protein expression, an arbitrary unit in Log2 scale. The cytokine serum levels have been reported earlier [ 18 ].…”
Section: Methodsmentioning
confidence: 84%
“…For example, a recent study by Astradsson et al demonstrated differential expression patterns of inflammatory proteins and immune response markers between patients that underwent surgery, radiotherapy and/or chemoradiation. This study showed that cisplatin-based chemoradiotherapy had immunological effects in HNSCC patients [ 42 ], whereas surgery alone did not. In our current study, we observed a significantly lower CRP level at the post-treatment follow-up in patients receiving surgery as only treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study was registered at ClinicalTrials.gov (NCT03343236). The present study is an extension of our earlier study aimed at determining the immune reaction to different treatment modalities [ 44 ].…”
Section: Methodsmentioning
confidence: 99%